Слідами Бозької археологічної експедиції 1930—1932 рр. - Товкайло, М.Т. (Археологія і давня історія України, 2017)
Бозька археологічна експедиція 1930—1932 рр.
відкрила новий етап у дослідженні археологічних пам'яток у Середньому Побожжі: було виявлено
і досліджено низку різночасових і різнотипових пам'яток, які заставили по-новому поглянути на
давню історію цього регіону, здобуто великий масив археологічних матеріалів. Божская археологическая экспедиция 1930—1932 гг. открыла новый этап в исследовании археологических
Среднего Побужья (верхнее и среднее
течение реки Южный Буг): было обнаружено и исследовано ряд разновременных и разнотипных памятников, которые заставили по-новому взглянуть
на древнюю историю этого региона, добыто большой
массив археологических материалов.
Экспедиция создана и действовала в условиях
террора в различных его проявлениях, что было
главным и постоянным методом государственного управления от октябрьского переворота 1917 по
1991 гг. В следствие погрома украинской археологической науки, репрессий и физического уничтожения самых исследователей-археологов, материалы экспедиции не были должным образом опубликованы. Трагически сложилась судьба большинства
участников экспедиции. Погибла большая часть материалов их исследований. Не сохранилась и значительная часть полевой документации (дневники, чертежи и фотографии). Однако, не погибла память об исследователях, и мы должны по достоинству оценить их достижения. This essay is dedicated to the memory of an entire
galaxy of Ukrainian researchers — archaeologists,
who in 1930—1932 worked in the Boz′koп archeological
expedition. These works expedition opened a new
stage in the study of archaeological to Monuments of
the average Pobozhzhi: Was discovered and investigated
several explanatory and different type of monuments.
What things moving with an new insight into
a long history of this region, Earned a large number of
archaeological materials.
Expedition — was organized and worked in the
conditions of terror in different domains, who was the
chief and permanent method of public administration
from the October coup in 1917 and 1991. Through the mayhem of archaeological science, repression and
physical extermination of most archaeologists, materials research Boz′koп the expedition had not been properly
published. Tragic situation, the fate of most of the participants of the expedition. Killed most of the materials
of their research. Similarly, not preserved and most records, drawings and photographs. However, not
killed the memory about them and we need to properly evaluate their achievements.